Minorities in International Law - Chinchón Álvarez, Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This article offers an examination of the term minority from the international law perspective. For this purpose, an initial analysis will be carried out trying to configure its current conceptualization based on the development that has taken place especially since the League of Nations age. This will be followed by the fundamental notes regarding the international legal regime applicable to minorities, distinguishing between this concept, peoples and the indigenous peoples. Finally, it will be concluded with a brief reflection in light of all this issues and the reality that minorities currently face according to the international bodies themselves.